Design and Development of Animal Recognition Application Using Gamification and Sattolo Shuffle Algorithm on Android Platform - Samuel Christoper Santo; Ni Made Satvika Iswari (Universitas Multimedia Nusantara, 2017)
Information and communication technology has been developed rapidly and affectedvarious aspects such as propagation of information and marketing strategy of tourist attraction. KebunBinatang Ragunan is one of tourist attraction in Indonesia. Aside from recreation area, Kebun BinatangRagunan can be a place to learn animals. However, learning animals itself tends to be less attractive and less interactive. Therefore, an application was developed as one of animal learning media to increase touristmotivation. The application developed in form of quiz game by using gamification like achievement to increase their motivation in animals learning and using Sattolo Shuffle algorithm in order to make quiz more varied. After testing, the application is known affect the Behavioral Intention to Use level around 76.96% and Immersion level around 82.43% in giving motivation and attracting tourist attention to use the application. Sattolo Shuffle algorithm successfully applied in application to produce a unique sequence of each randomized quiz. Keywords—Achievement, Animal Recognition, Gamification, Quiz Game, Sattolo Shuffle. REFERENCES [1] Egger, R. 2012. The impact of near field communication on tourism. In Journal of Hospitality and Tourism Technology, 4(2), p. 119-133. [2] Undang-Undang Republik Indonesia. 2009. Undang-Undang Republik Indonesia Nomor 10 Tahun 2009 [online]. Available in: http://peraturan.go.id/uu/nomor-10-tahun-2009.html [accessed on 21 March 2016]. [3] World Travel Market. 2011. WTM Global Trends Report 2011. Available in: http://www.toposophy.com/files/1/files/onsite_global_trends_ v3_lo.pdf [accessed on 13 April 2016]. [4] Deterding, S., Khaled, R., Nacke, L.E., and Dixon, D. 2011. Gamification: Toward a Definition. CHI 2011 Workshop Gamification: Using Game Design Elements in Non-Game Contexts[online]. Available in: http://gamificationresearch.org/wpcontent/uploads/2011/04/CHI_2011_Gamification_Workshop .pdf [accessed on 21 March 2016]. [5] Xu, F., Tian, F., Buhalis, D., Weber, J., and Zhang, H. 2015. Tourist as Mobile Gamers: Gamification for Tourism Marketing. In Journal of Travel and Tourism Marketing. [6] Sattolo, S. 1986. An Algorithm to Generate a Random Cyclic Permutation. Information Processing Letters, 22(6), p. 315- 317. [7] Zichermann, G. and Cunningham, C. 2011. Gamification by Design: Implementing Game Mechanics in Web and Mobile Apps.First edition. O'Reilly Media, Inc., Sebastopol, California [8] Kapp, K.M. 2012. The Gamification of Learning and instruction: Game-based Methods and Strategies for Training and Education. Pfeiffer, San Fransisco, CA. [9] Bunchball. 2012. What is Gamification? Available in: http://www.bunchball.com/gamification [accessed on 23 March 2016]. [10] Wilson, M.C. 2004. Overview of Sattolo's Algorithm. New Zealand, Auckland. [11] Lowry, P.B., Gaskin, J.E., Twyman, N.W., Hammer, B., and Roberts, T.L. 2013. Taking